Usefulness of serum albumin as a prognostic factor in dengue - H., Murali B.; Lysander, Shilpa Deborah; Nannapaneni, Meghana (International Journal of Contemporary Pediatrics, 2020)
Background: Dengue is a major public health problem throughout subtropical and tropical regions. In more severe or complicated dengue, patients present with a severe febrile illness characterized by abnormalities of hemostasis and increased vascular permeability, which in some instances results in a hypovolemic shock. Dengue is endemic in more than 100 countries in tropical and subtropical regions with an estimated 390 million infections occurring worldwide, among which 96 million infections are clinically apparent. The objective of this study is to assess the usefulness of serum albumin as a prognostic factor in dengue. Method: This observational study enrolled 100 patients who were admitted in KIMS Hospital from June 2017 to June 2018 without any co morbidities as mentioned in the exclusion criteria. On day 4 of illness hemoglobin, packed cell volume, platelet and serum albumin were done, and the participants were classified into 3 groups based on clinical manifestation Results: In this study, hemoglobin was elevated on day 4 in group 3 when compared to other groups and it was statistically significant. Hemoconcentration and low platelet values were also seen in group 3 when compared to other groups showing statistical significance. Serum albumin was also low in group 3 when compared to other groups, which was strongly significant. Conclusion: Hence serum albumin can be used as a prognostic factor in dengue.